Muslim diaspora and its representation in selected post-9 11 literary works - Sulaiman, Suraiya; Quayum, Mohammad Abdul (IIUM Press, International Islamic University Malaysia, 2017)
This book is a qualitative, non-empirical, textual and contextual study of six literary works by writers of the Muslim diaspora from the UK and the US published in the aftermath of the 9/11 event. The texts selected are Monica Ali’s Brick Lane (2003), Khaled Hosseini’s The Kite Runner (2003), Leila Aboulela’s Minaret (2005), Mohsin Hamid’s The Reluctant Fundamentalist (2007), Mohja Khaf’s The Girl in the Tangerine Scarf (2007) and Robin Yassin-Kassab’s The Road from Damascus (2009). By employing the Postcolonial theoretical framework, with an emphasis on diaspora studies and Islamic feminism, this book investigates the experiences of diasporic Muslims in the UK and the US with regard to identity conflict, notions of homeland, “imaginary homeland” and unstable home, as well as the concepts of hybridity, Third Space and ummatic identity. It also explores how the selected literary works subvert the notions of Islamophobia and negotiate the idea of Islamic “fundamentalism,” as well as the negative representation of Muslim women. An in-depth analysis of the texts reveals that diasporic Muslims often experience identity conflict and nostalgia towards their homeland, although in varying degrees. Nevertheless, many of them negotiate their Muslim identities within their surrogate societies by creating a sense of hybridity and a Third Space from the meeting of cultures. Some Muslims also employ the notion of ummatic identity to help strengthen the bond among diasporic Muslims and negotiate a sense of belonging within their diasporic space. It becomes apparent from the selected texts that literary works may help bridge the gap of understanding between diasporic Muslims and their host societies. Lastly, the analysis shows that these literary works help dismantle the negative representations of Muslim women by depicting various aspects of their lives and identities. From an Islamic feminist angle, it is evident that some diasporic Muslim women are still affected by patriarchal practices persisting in many Muslim communities. However, the novels demonstrate that some Muslim women are empowered by the teachings of Islam, and this helps them destabilise the patriarchal worldview, formulate their identities and regain their dignity as true believers.